2017
DOI: 10.1039/c7tc01234a
|View full text |Cite
|
Sign up to set email alerts
|

Densely grafted liquid crystalline copper phthalocyanine side chain polymer: synthesis and characterization

Abstract: Synthesis and characterization of a liquid crystalline polymer with pendant copper phthalocyanine side chains (PCuPc).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…For both [CH‐Pc][Ps] and [CD‐Pc][Ps], the reciprocal d ‐spacings of the sharp small‐angle reflections relate to each other are 1:3 1/2 :2, which are indicative of a columnar phase with a hexagonal lattice Col h . [ 39–41 ] In the wide angle region, the broad halos presented at high angles around 2 θ ≈ 22 ° are associated with the inter disk distance ( c = 4.0 Å for [CH‐Pc][Ps] or 4.1 Å for [CD‐Pc][Ps]) in a 1D molecular stack. However, the series of diffraction peaks at small angles disappear to resemble that of an isotropic phase, indicating formation of nematic discotic phase.…”
Section: Resultsmentioning
confidence: 99%
“…For both [CH‐Pc][Ps] and [CD‐Pc][Ps], the reciprocal d ‐spacings of the sharp small‐angle reflections relate to each other are 1:3 1/2 :2, which are indicative of a columnar phase with a hexagonal lattice Col h . [ 39–41 ] In the wide angle region, the broad halos presented at high angles around 2 θ ≈ 22 ° are associated with the inter disk distance ( c = 4.0 Å for [CH‐Pc][Ps] or 4.1 Å for [CD‐Pc][Ps]) in a 1D molecular stack. However, the series of diffraction peaks at small angles disappear to resemble that of an isotropic phase, indicating formation of nematic discotic phase.…”
Section: Resultsmentioning
confidence: 99%
“…Pcs have been incorporated in such systems as a side group, as a terminal group, in the main chain and in a polymeric network [21][22][23][24][25][26]. Kimura et al studied the self-assembly properties of ZnPc-terminated Butyl Acrylate (BA) and Tri(Ethylene Glycol)Methyl Ether Acrylate (TEGA) polymers and have reported formation of nanofibers through self-organization [18].…”
Section: Introductionmentioning
confidence: 99%
“…30 Thelakkat et al reported the synthesis and characterization study of a soluble and hydrophilic semiconductor, in which they used grafting-to of a nonsymmetrical copper Pc with azide functionality to a styrene backbone. 31 Recently, our group reported the synthesis of a new functional polystyrene polymer with a zinc Pc terminal that involved a click reaction between nonsymmetrical terminal-alkynyl-containing zinc Pc and azide-end functional polystyrene. 32 Poor solubility and slippery π − π stacks restricted the applications of Pcs.…”
Section: Introductionmentioning
confidence: 99%